(untitled) (Academic Journal of Internal Affairs, 2021)
In the 67th year of her life, Prof. dr. Andrea Kozáry, a professor at the Faculty of Law Enforcement of the University of Public Service, one of the founders of the Hungarian Law Enforcement Society, a member of the Law Enforcement Subcommittee of the Hungarian Academy of Sciences, a key figure of researches in Hungarian law enforcement, deceased. Prof. dr. László Korinek, President of the Hungarian Law Enforcement Society, bids farewell in this necrology.